RANCANG BANGUN SISTEM TRANSMISI PADA MESIN PENGIRIS BAWANG MERAH DAN BAWANG BOMBAY TENAGA HIBRID - Arditama, Ridwan; Saleh, Agus (Jurnal Mahasiswa Terapan, 2024)
Design is the planning of all systems related to the nature of machines, analysts, products, structures and tools. The design stages are made important decisions that affect the results of the design itself, so that before the product is made, a planning process, flow, design that can be understood by all those involved in the process of making the product is carried out. Pulley and V-Belt were chosen as the transmission system in the shallot and onion slicing machine has several advantages, namely it does not cause noise, low maintenance costs compared to using a gear and chain drive transmission system, while the disadvantages of using pulley and v-belt transmission systems are that the power generated is not so strong as the use of gear movement and can only be used in machines that use simple power. The method chosen to design the transmission system is by measuring, observing and calculating, then analyzing the data so as to obtain an overview of the performance of the machine which in turn can provide specifications for the needs of the machine to be made. From the transmission system can be produced a rotation that can help design machines in any concept such as chopping, cutting, grinding, grinding and others.